In demand during a crisis: Advising well in exceptional circumstances; Gefragt in der Krise: Gut beraten unter Ausnahmebedingungen - Oliver Ibert; Tjorven Harmsen; Verena Brinks (Leibniz-Institut für Raumbezogene Sozialforschung (IRS), 2021)
Handling crises means, above all, having to make decisions under conditions of existential threat, fundamental uncertainty, and great urgency. Modern crises transgress territorial and disciplinary boundaries, administrative departments, and economic sectors, as well as the boundaries between culture and nature. Elected officials are thus ever more frequently confronted with the limitations of their own knowledge. External expertise can therefore be of assistance in making well-informed decisions before, during, and following a crisis. Dealing with crises is no longer only about averting urgent threats, but also about reflection upon them and, ideally, making changes to prevent their recurrence. It is here that experts can also make their contribution. Where one succeeds in coming out of a crisis stronger than before, one can speak of resilient crisis management. Unfortunately, there is barely any knowledge about the particularities of crisis consultancy. The following recommendations are intended to prepare experts to act adequately in such exceptional situations. They can serve during times of non-crisis as preparation for tasks ahead or be used for quick orientation when a crisis arises. – – Der Umgang mit Krisen bedeutet vor allem, Entscheidungen unter Bedingungen von existentieller Bedrohung, fundamentaler Unsicherheit und hoher Dringlichkeit treffen zu müssen. Moderne Krisen überschreiten territoriale und disziplinäre Grenzen, Verwaltungsressorts und Wirtschaftssektoren oder die Grenze zwischen Kultur und Natur. Mandatsträger*innen sind daher immer häufiger mit den Grenzen ihres eigenen Wissens konfrontiert. Externe Expertise kann dabei helfen, vor, während und nach einer Krise gut informierte Entscheidungen zu treffen. Im Umgang mit Krisen geht es nicht mehr allein darum, eine akute Bedrohung abzuwenden, sondern auch Krisenerfahrungen zu reflektieren und idealerweise Veränderungen vorzunehmen, um ein Wiederkehren der Krise zu verhindern. Auch Expert*Innen können hierzu beitragen. Gelingt es, gestärkt aus einer Krise herauszukommen, dann sprechen wir von einem resilienten Krisenumgang. Über die Besonderheiten von Beratung in Krisen existieren leider kaum Kenntnisse. Diese Handreichung soll Experten*innen darauf vorbereiten, in solchen Ausnahmesituationen adäquat zu agieren. Sie kann in Nicht-Krisenzeiten als Vorbereitung auf eine Aufgabe gelesen oder im Krisenfall zur schnellen Orientierung herangezogen werden.
Keywords: 710